Array Comparative Genomic Hybridization Analysis Reveals Significantly Enriched Pathways in Canine Oral Melanoma - Brocca, Ginevra; Ferraresso, Serena; Zamboni, Clarissa; Martinez-Merlo, Elena M.; Ferro, Silvia; Goldschmidt, Michael H.; Castagnaro, Massimo (Frontiers in Oncology, 2019)
Human Mucosal Melanoma (hMM) is an aggressive neoplasm of neuroectodermal origin with distinctive features from the more common cutaneous form of malignant melanoma (cMM). At the molecular level, hMMs are characterized by large chromosomal aberrations rather than single-nucleotide mutations, typically observed in cMM. Given the scarcity of available cases, there have been many attempts to establish a reliable animal model. In pet dogs, Canine Oral Melanoma (COM) is the most common malignant tumor of the oral cavity, sharing clinical and histological aspects with hMM. To improve the knowledge about COM’s genomic DNA alterations, in the present work, formalin-fixed, paraffin-embedded (FFPE) samples of COM from different European archives were collected to set up an array Comparative Genomic Hybridization (aCGH) analysis to estimate recurrent Copy Number Aberrations (CNAs). DNA was extracted in parallel from tumor and healthy fractions and 19 specimens were successfully submitted to labeling and competitive hybridization. Data were statistically analyzed through GISTIC2.0 and a pathway-enrichment analysis was performed with ClueGO. Recurrent gained regions were detected, affecting chromosomes CFA 10, 13 and 30, while lost regions involved chromosomes CFA 10, 11, 22 and 30. In particular, CFA 13 showed a whole-chromosome gain in 37% of the samples, while CFA 22 showed a whole-chromosome loss in 25%. A distinctive sigmoidal trend was observed in CFA 10 and 30 in 25% and 30% of the samples, respectively. Comparative analysis revealed that COM and hMM share common chromosomal changes in 32 regions. MAPK- and PI3K-related genes were the most frequently involved, while pathway analysis revealed statistically significant perturbation of cancer-related biological processes such as immune response, drug metabolism, melanocytes homeostasis, and neo-angiogenesis. The latter is a new evidence of a significant involvement of neovascularization-related pathways in COMs and can provide the rationale for future application in anti-cancer targeted therapies.